Penerapan Perizinan Usaha Kegiatan Jasa Laundry Di Kecamata Barong Tongkok Kabupaten Kutai Barat - Eko Fransisco Valentino Ruitang; Siti Kotijah; Agustina Wati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Study Interest State Administrative Law, Implementation of Business Licensing for Laundry Services Activities in Barong Tongkok District, West Kutai Regency, under the guidance of Dr. Siti Kotijah S.H., M.H and Agustina Wati S.H., M.H. Business licensing is an important aspect in the implementation of business activities, including laundry service businesses that are increasingly growing in urban communities. Laundry businesses require official permits from the local government as a form of compliance with regulations governing economic activities and environmental protection. With licensing, the government can supervise business activities and ensure that business actors comply with operational standards, including in the management of domestic waste generated from the washing process. Laundry business licensing is also an instrument to ensure consumer safety and comfort. Business permits include technical and administrative requirements, such as location permits, environmental permits (UKL-UPL/SPPL), and operational permits from related agencies such as the Investment and One-Stop Integrated Services Agency (DPMPTSP). Without complete permits, business actors can be subject to administrative sanctions to criminal penalties, as regulated in various laws and regulations such as Law Number 32 of 2009 concerning Environmental Protection and Management. Research on laundry business permits is important to provide a comprehensive picture of the processes, obstacles, and legal and environmental implications that may arise if business actors do not comply with applicable licensing provisions. Social legal research, with field studies at the Investment and One-Stop Integrated Service Office of West Kutai Regency, Barong Tongkok District and Laundry businesses in Barong Tongkok, West Kutai. Laundry businesses that have permits are 7, while there are still many laundry businesses that do not have laundry business permits. Business actors do not have business permits, because the reason is that their business is small, and the permit process is very difficult, and business actors avoid paying local taxes.